Epidermolysis bullosa acquisita: current diagnosis and therapy - Christine R. Mehren; Robert Gniadecki (PAGEPress Publications, 2011)
Epidermolysis bullosa acquisita (EBA) is an acquired, autoimmune subepidermal blistering disease with an approximate prevalence of 0,2/million people. The hallmark of EBA is the presence of autoantibodies (mainly IgG class) to anchoring fibril collagen (type VII collagen) located at the dermal-epidermal junction. Clinically EBA is subdivided into the inflammatory and the non-inflammatory phenotypes, depending on the level of the cleavage in the basal membrane. A recent addition to the diagnostic techniques is the analysis of the serration pattern of the autoantibody deposits at the basal membrane in the direct immunofluorescence. EBA and the closely related bullous systemic lupus erythematosus are the only diseases presenting with the so-called u-serration pattern which distinguishes them from many other autoimmune subepidermal blistering diseases. We also discuss the recent advances in therapy, including the experience with Rituximab.